Pengaruh sumber daya manusia, pemanfaatan teknologi informasi dan pengawasan keuangan daerah terhadap keandalan pelaporan keuangan pemerintah kota dumai - Gita Silvia Marda; Raja Adri Satriawan; Supriono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to examine and obtain empirical evidence about the factors that affect the reliability of financial reporting local government, specifically her at Dumai City Government. This research is motivated by the fact that the government financial reporting should provide information which is reliable in assessing accountability and decision-making parties. Variables to be tested in this study were, among others, the quality of human resources, the utilization of information technology and financial control systems area (as independent variables) to the reliability of financial reporting (as dependent variable).The data in this study is primary data obtained from questionnaires distributed directly to the respondents. Data collected from 105 respondents who work in finance / administration on regional work units (SKPD) in the city of Dumai. This hypothesis was tested by multiple linear regression using partial hypothesis test (ujit-t).The test results showed that the quality of human resources and financial controls areas significant positive effect partially on local government financial reporting reliability of Dumai. While Information Technology bepengaruh not to Keandalaan Financial Reporting for maximum utilization of Information Technology has not used in Dumai City government institutions.Keywords: Human Resources, Information Technology, Regional Financial Supervision and Financial Reporting Reliability Government